ANALISIS PENGGANTIAN BACKHOE TAHUN PEMAKAIAN KELIMA DENGAN METODE NET ANNUAL VALUE PADA PT IFISHDECO - Raymon Andre Maraya; Juanita R. Horman (Jurusan Teknik Pertambangan Program Studi S1 Teknik Pertambangan Fakultas Teknik Pertambangan dan Perminyakan Universitas Papua, 2020)
PT Ifishdeco is a mining company that uses backhoe Sany SY-365 in its demolition activities. One of backhoes used has the greatest mechanical avaibility compared to others, so it is necessary to analyze the replacement of equipment in order to know the right time for replacement. The method used is the engineering economic method of Net Annual Value (NAV) with the concept of ‘defender’ and ‘challenger’ to analyze the cost and benefits of the equipment that can be distributed anually. To determine the NAV of an equipment and to know the the right time for replacement, it is necessary to know how much revenue and cost required for the backhoe to operate during the replacement of the old backhoe (defender) with a new backhoe (challenger) by conducting a replacement experiment in the first year after the tool operates until the end of the project life. The calculation results indicated that the replacement of equipment is more profitable at the sixth year of the project time, with NPV value of USD 29,530,448.96 and NAV value of USD 4,012,241.81.